An influence of physical rehabilitation on living standards of children with chronic heart failure - Maryana Chekhovska; Liubov Chekhovska (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the impact of the developed program of physical rehabilitation on the quality of life of school-age children with chronic heart failure (CHF) I-IIA stages. Material & Methods: analysis, generalization of scientific and methodological literature, Internet, survey method, methods of mathematical statistics. The study was conducted on the basis of the West-Ukrainian specialized children's medical center (Lviv). The experiment involved 34 school-age children with CHF I-IIA stages. Result: the evaluation of the quality of life of school age children with EH with CHF I-IIA stages showed a significant improvement in the four blocks. The physical functioning according to the parents' information had the greatest improvement. Despite the increase in the indicator of the functioning of the child in school, it remains low. Improving emotional and social functioning contributes to the social adaptation of children in society. The positive and negative dynamics of QoL of children of CHF for block indicators is not reliably confirmed. Conclusion: quality of life in children with CHF is an important integral indicator.